The effect of oral ondansetron on QT interval in children with acute gastroenteritis; a retrospective observational study - Heewon Yang; Woochan Jeon; Yura Ko; Sooin Jeong; Jisook Lee (BMC, 2021)
Abstract Background In mildly to moderately dehydrated patients with acute gastroenteritis (AGE), oral rehydration therapy (ORT) is the treatment of choice. Though ondansetron is a very effective antiemetics and leads to succeed ORT, there have been reports QT prolongation in patients using it. We investigated the effect of oral ondansetron on QT interval in mildly to moderately dehydrated children with AGE. Methods This retrospective observational study was conducted in a single pediatric emergency department (ED) of a tertiary university hospital. We collected the medical records of patients with a primary diagnosis of AGE who received oral ondansetron and underwent an electrocardiogram between January 2017 and June 2018. A pediatric emergency physician calculated the corrected QT interval (QTc) by Bazett's method, and the calculations were reviewed by a pediatric cardiologist. QTc values before (preQTc) and after (postQTc) ondansetron administration were analyzed. ΔQTc was calculated as the change from preQTc to postQTc. We also investigated any cardiac complications from oral ondansetron. Results Total 80 patients were included. The mean age of the patients was 53.31 ± 32.42 months, and 45% were male. The mean dose of oral ondansetron was 0.18 ± 0.04 mg/kg. The mean interval from administration of ondansetron to performance of the electrocardiogram was 65 ± 26 min. The mean preQTc was 403.3 ± 24.0 ms, and the mean postQTc was 407.2 ± 26.7 ms. Two patients had a preQTc ≥460 ms, and one patient had a postQTc ≥460 ms. ΔQTc was ≥30 ms in seven patients (8.8%). No ΔQTc was ≥60 ms. No pre- or postQTc was ≥500 ms. No patient had a fatal cardiac arrhythmia after taking ondansetron. Conclusion Oral administration of a single dose of ondansetron in children with AGE did not cause high-risk QTc prolongation or fatal arrhythmia.